A Modernizing Empire? Politics, Culture and Economy in Portuguese Late Colonialism - Jerónimo, Miguel Bandeira (2015)
The politics and policies of late colonialism in the Portuguese empire were characterized by a repressive developmentalism, a particular combination of enhanced coercive (symbolic and material) repertoires of rule, programmed developmental strategies of political, economic and sociocultural change, and processes of engineering of socio-cultural differentiation. At its core, as Frederick Cooper noted, was a 'repressive version of the developmentalist colonial state. The late imperial and colonial states aimed to co-ordinate policies of imperial resilience in a context of widespread evolving colonial and international pressures which were contrary to their existence, or pressing for their substantial reform.2 They were the institutional loci in which the entangled policies of repressive developmentalism evolved, in which there was a coalescence between idioms, programmes, and repertoires of colonial social control and coercion (for instance, the schemes of resettlement, civil and military, of the African population and the strategies of counter-insurgency) - related, but not reducible, to the colonial wars and to the militarization of colonial societies; idioms, programmes, and repertoires of colonial development and modernization (for instance, the developmental plans of the 1950s and 1960s); and idioms, projects, and repertoires of imperial and colonial social engineering (for instance, tllre indigennto regime or the nationalized version of the doctrine of welfare colonialism and its languages and programmes of native welfare and native social promotion).